2016
DOI: 10.1103/physreve.93.022601
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium fluid-crystal interfacial free energy of bcc-crystallizing aqueous suspensions of polydisperse charged spheres

Abstract: The interfacial free energy is a central quantity in crystallization from the metastable melt. In suspensions of charged colloidal spheres, nucleation and growth kinetics can be accurately measured from optical experiments. In previous work, from these data effective nonequilibrium values for the interfacial free energy between the emerging bcc nuclei and the adjacent melt in dependence on the chemical potential difference between melt phase and crystal phase were derived using classical nucleation theory (CNT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 171 publications
(360 reference statements)
0
8
0
Order By: Relevance
“…The typical time and length scales of colloidal systems allow for time-resolved observations of solidification with easily manageable experimental techniques, even real space imaging of nucleation events with 'atomic' resolution [41, 42, [43]. More recently, it was demonstrated from scattering experiments that also the thermodynamics of crystallization can be accessed in a quantitative manner and the Turnbull coefficients of bcc forming metals and colloids are very similar [44]. That stresses the applicability of colloidal suspensions as model systems for nucleation studies, which are not directly applicab systems.…”
Section: Ducting Materials If the Eriences A Timementioning
confidence: 99%
See 1 more Smart Citation
“…The typical time and length scales of colloidal systems allow for time-resolved observations of solidification with easily manageable experimental techniques, even real space imaging of nucleation events with 'atomic' resolution [41, 42, [43]. More recently, it was demonstrated from scattering experiments that also the thermodynamics of crystallization can be accessed in a quantitative manner and the Turnbull coefficients of bcc forming metals and colloids are very similar [44]. That stresses the applicability of colloidal suspensions as model systems for nucleation studies, which are not directly applicab systems.…”
Section: Ducting Materials If the Eriences A Timementioning
confidence: 99%
“…The scheme according to Figure 27 is further used to estimate the molar entropy of fusion [44]. It is assumed that ∆S f does not change with increasing metastability, i.e., with increasing particle number density.…”
mentioning
confidence: 99%
“…In principle, polydispersity could make this difference. In a recent study we observed a clear anti-correlation between size-polydispersity and the interfacial free energy involved in homogeneous nucleation 89 . Therefore, we carefully checked the low nominal polydispersity index of the present system of PI = 0.011 with several additional measurements to find a corrected value of PI ≈ 0.05 (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…where the subscripts fcc, bcc and fcc-bcc refer to the fcc-fluid, bcc-fluid and fcc-bcc interfaces with γ bcc ≈ 0.12 k B T a 2 and γ fcc ≈ 0.40 k B T a 2 [46] with an extended comparison of experimental and theoretical values provided by [45]. The angles refer to the directions of the interfaces close to the triple junction.…”
mentioning
confidence: 99%
“…In these systems, a face-centered cubic (fcc) crystal, a bodycentered cubic (bcc) crystal and a fluid can coexist. Colloids have long been used as model systems to explore such situations, including nucleation [26][27][28][29], crystallization [30][31][32][33][34], melting [16,35,36], defects [37], glass transition [38][39][40][41], solid-liquid interfaces [42][43][44][45][46], solid-solid phase transformations [47][48][49][50] as well as the microscopic response to external forces [51][52][53][54].…”
mentioning
confidence: 99%